PROTECTING CITIZENS IN BORDER TERRITORY BASED ON HUMAN RIGHTS - Endah Rantau Itasari (Universitas Pendidikan Ganesha, 2021)
Recognition and protection of human rights is one of the characteristics of a rule of law. The State of Indonesia is a state based on law in accordance with the provisions of Article 1 paragraph 3 of the 1945 Constitution